(3GdHMK GdYdej hESJNOGe eUGOQ GdeYdheGJ GdJbdjOjI hGdEdcJQhfjIs - (3YGeQ(B, (3bfOjdLjs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2008)
(3jVe JGQjN GdHMK GdYdej heSJdReGJg hCfhGYg, NWI GdHMK GdYdej hNWhGJ EYOGOg, efGgL GdHMK GdYdej, GdeYGjfI h GdYjfGJ, EYOGO JbQjQ GdHMK GdfgGFj Gdecj, eUGOQ GdeYdheGJ GdEdcJQhfjI h GdEfJQfjJ, GdehGbY GdHMKjI GdEdcJQhfjI Ydi GdEfJQfjJ , JhKjb GdeUGOQ hGdeYdheGJ aj JbQjQ GdHMK , ESJNOGe GdecJHI hagGQSgGs
Keywords: (3GdHMhK GdYdejIs; (3NOeGJ GdeYdheGJs; (3WQb GdHMKs